Menganalisis Pengelolaan Manajemen Tenaga Pendidik dan Kependidikan: Strategi, Faktor Penghambat, dan Solusi Pada Pondok Pesantren Terpadu Raudhatul Jannah - Sani Susanti; Arisma Laily Na Imah; Dian Patricia Natalia Lubis; Siti Maulida J; Rizka Khairunnisa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Educational staff management is the process of planning, organizing, mobilizing, and controlling teachers and all components within an educational institution to achieve objectives effectively and efficiently. This article uses a descriptive and qualitative approach by collecting primary and secondary data through interviews, observations, and documentation. The main issues examined in this research are considerations in the placement and assignment of educational staff, as well as the impact of financial conditions on the management of educational staff. The purpose of this research is to find solutions to existing problems in the management of educational staff so that these issues can be addressed. The results of the study show that in the placement and assignment of educational staff, factors that need to be considered include educational background, teaching experience, competence, and the needs of the institution. Additionally, financial conditions significantly influence the management of educational staff, including the provision of facilities, professional development, and teacher welfare. To address these problems, strategic efforts are needed, such as thorough planning of educational staff needs, the development of a transparent evaluation and promotion system, and the adequate allocation of budgets for teacher welfare and professional development. Thus, the management of educational staff can run more effectively and efficiently, allowing educational goals to be optimally achieved.